2010
DOI: 10.4161/chan.4.5.12874
|View full text |Cite
|
Sign up to set email alerts
|

Splice-variant changes of the CaV3.2 T-type calcium channel mediate voltage-dependent facilitation and associate with cardiac hypertrophy and development

Abstract: Low voltage-activated T-type calcium (Ca) channels contribute to the normal development of the heart and are also implicated in pathophysiological states such as cardiac hypertrophy. Functionally distinct T-type Ca channel isoforms can be generated by alternative splicing from each of three different T-type genes (Ca(V)3.1, Ca(V)3.2,Ca(V)3.3), although it remains to be described whether specific splice variants are associated with developmental states and pathological conditions. We aimed to identify and funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 63 publications
2
57
0
Order By: Relevance
“…Re-expression of fetal I Ca, T in the ventricular myocytes during pathological hypertrophy is well established (22,23,42). Studies have demonstrated the expression of the Ca v 3.2 (␣ 1H ) channel current responsible for the development of cardiac hypertrophy (27,44) and the expression of the Ca v 3.1 (␣ 1G ) channels is attributed to anti-hypertrophic effect and cardioprotective function (45). It was reported that in pathological hypertrophy the Ca 2ϩ influx via the re-expressed Ca v 3.2 channel initiates the binding of calcineurin to the C terminus of Ca v 3.2 leading to activation of NFAT (46).…”
Section: Discussionmentioning
confidence: 99%
“…Re-expression of fetal I Ca, T in the ventricular myocytes during pathological hypertrophy is well established (22,23,42). Studies have demonstrated the expression of the Ca v 3.2 (␣ 1H ) channel current responsible for the development of cardiac hypertrophy (27,44) and the expression of the Ca v 3.1 (␣ 1G ) channels is attributed to anti-hypertrophic effect and cardioprotective function (45). It was reported that in pathological hypertrophy the Ca 2ϩ influx via the re-expressed Ca v 3.2 channel initiates the binding of calcineurin to the C terminus of Ca v 3.2 leading to activation of NFAT (46).…”
Section: Discussionmentioning
confidence: 99%
“…Of the three different T-type Ca 2ϩ channel isoforms reported, alternative splicing of the Ca v 3.2 channels results in functional diversity of the channel during cardiac development (47). Recent findings using a heterologous expression system of HEK293 cells suggest a complex regulation for the Ca v 3.2 channels.…”
Section: Discussionmentioning
confidence: 99%
“…69 The expression of Ca V 3.2 splice variants was found to be regulated during development, as well as in the LV of hypertrophic rat hearts. Furthermore, splice variants of Ca V 3.2 channels displayed alterations in function that could be relevant with respect to contractile performance in the diseased heart.…”
Section: Expression Of T-type Ca 2+ Channels In Right-sided Heart Faimentioning
confidence: 95%